(untitled) - Hahn, Steven (Birmingham, England, 1998)
All distributed applications need to know where resources are to be able to use them. Active Directory is the mechanism for tracking resources (components, applications, users etc.) wherever they are on distributed networks. This is a book for experienced systems developers and programmers who would like to use HTTP (the protocol of the Internet) to deliver sophisticated system level solutions using light-weight client browsers. Described in the book are applications, with code samples, that use Active Directory to manage users and user-groups, system services, file services, and the print queue. Although Active Directory can be used to access and manage different systems (NT 4.0, NT 5.0 (beta), NDS, LDAP Compliant, etc.) all of the code in this book will be using the NT 4.0 Server as a target system
Keywords: Lập trình Internet,Internet programming